2011
DOI: 10.1159/000330746
|View full text |Cite
|
Sign up to set email alerts
|

Liver Transplantation for Hepatocellular Carcinoma – Is There a Risk of Recurrence Caused by Intraoperative Blood Salvage Autotransfusion?

Abstract: Background/Aims: The use of intraoperative blood salvage autotransfusion (IBSA) during surgical approaches may contribute to tumour cell dissemination. Therefore, IBSA should be avoided in cases of malignancy. However, the risks of IBSA might be acceptable in liver transplantation (LT) for selected small hepatocellular carcinoma (HCC). Methods: In total, 136 recipients of LT with histologically proven HCC in the explanted liver were included in this analysis. With regard to tumour recurrence, 40 patients recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 62 publications
0
68
0
Order By: Relevance
“…The sequence of these studies confirmed the three steps which forms ''a logical sequence for proofof-concept.'' There were two other recent studies by hepatobiliary oncologists where they reinfused salvaged blood in 40 patients [27] and 121 patients [17] undergoing liver Eur Spine J transplantation for hepatocellular carcinoma. They also concluded that salvaged blood was safe for reinfusion.…”
Section: Discussionmentioning
confidence: 99%
“…The sequence of these studies confirmed the three steps which forms ''a logical sequence for proofof-concept.'' There were two other recent studies by hepatobiliary oncologists where they reinfused salvaged blood in 40 patients [27] and 121 patients [17] undergoing liver Eur Spine J transplantation for hepatocellular carcinoma. They also concluded that salvaged blood was safe for reinfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative or postoperative autotransfusion can also be combined with preoperative ABT in elective major surgeries to improve the effect of blood transfusion and the prognosis of patients (36). Intraoperative or postoperative autotransfusion applications in cancer surgery remain controversial, since some clinicians fear that it may cause cancer cell proliferation and metastasis (37,38). However, other studies have revealed that it can be safely applied to certain tumor surgeries (39), with the required specific assessments before and during surgery such as tumor metastasis and recurrence, and the use of a leukocyte filter (40 -42).…”
Section: Intraoperative or Postoperative Autotransfusionmentioning
confidence: 99%
“…The authors also highlighted the correlation between CTC-levels and HCC prognosis after liver tumor's resection or hepatic artery chemoembolization [135]. Unlike several studies in the context of liver resection, relationship between CTC-presence and HCC recurrence after liver transplantation (LT), has not been extensively described yet [136, 137]. Indeed further investigations of CTCs in LT clinical setting would certainly provide valuable information for prediction HCC prognosis after transplantation.…”
Section: Ctcs and Liver Cancermentioning
confidence: 99%